Evidence of hydroxyurea activity in children with pretreated desmoid‐type fibromatosis: A new option in the armamentarium of systemic therapies. Issue 1 (30th September 2018) - Ferrari, Andrea; Orbach, Daniel; Affinita, Maria Carmen; Chiaravalli, Stefano; Corradini, Nadege; Meazza, Cristina; Bisogno, Gianni; Casanova, Michela
Abstract: Introduction: The treatment paradigm in desmoid‐type fibromatosis (DF) has changed in recent years from a surgery‐based strategy to a multidisciplinary approach that includes systemic therapies. Among various medical therapies, hydroxyurea has been considered of potential interest. This case series summarizes the experience gained at four centers using hydroxyurea in relapsing DF. Methods: Eligibility requirements were age < 21 years, histologically confirmed DF, and progressive or recurrent disease after at least one line of systemic therapy. Hydroxyurea was given orally at an initial dose of 20 mg/kg/day (escalated up to 30 mg/kg/day as necessary, if well tolerated). Results: The series included 16 patients treated between 2008 and 2016. Hydroxyurea was the second systemic therapy in nine cases, and the third (at least) in seven. There was no reported G3–G4 hematological toxicity, and one case of G3 diarrhea. Dose reductions were reported in three cases (due to G2 neutropenia). The response rate was 18.7% major partial remissions, 37.5% considering any amount of shrinkage, 68.7% considering symptom response or signs of tissue response as well. In patients with no progression, the treatment was continued for 9–24 months. Conclusion: This is the first published series on the efficacy of hydroxyurea in pediatric DF. The response rate was moderate, but similar to that reported for other medical therapies currently considered as treatment options in this disease. Though further, larger series are needed to confirm as much, hydroxyurea has potential as an effective alternative therapy for DF.